2013
DOI: 10.1136/neurintsurg-2013-010780
|View full text |Cite
|
Sign up to set email alerts
|

Admission neutrophil–lymphocyte ratio predicts 90 day outcome after endovascular stroke therapy

Abstract: Objective Immune dysregulation influences outcome following acute ischemic stroke (AIS). Admission white blood cell (WBC) counts are routinely obtained, making the neutrophil–lymphocyte ratio (NLR) a readily available biomarker of the immune response to stroke. This study sought to identify the relationship between NLR and 90 day AIS outcome. Methods A retrospective analysis was performed on patients who underwent endovascular therapy for AIS at West Virginia University Hospitals, Morgantown, West Virginia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 22 publications
7
127
0
1
Order By: Relevance
“…However, after performing multivariate regression analysis, we found that the NLR was not an independent predictor for 90-day mortality with considering other factors. Compared with the 90-day poor outcomes, NLR was not an independent predictor for 90-day mortality and the risk of 90-day mortality was also influenced by other factors, such as age, history of myocardial infarction and National Institute of Health stroke scale (NIHSS) [20,21]. One study [21] found the history of myocardial infarction and NIHSS had a higher OR (2.26 and 1.18) for 90-day mortality, and the NLR had a weaker predictive ability with OR of 1.08.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, after performing multivariate regression analysis, we found that the NLR was not an independent predictor for 90-day mortality with considering other factors. Compared with the 90-day poor outcomes, NLR was not an independent predictor for 90-day mortality and the risk of 90-day mortality was also influenced by other factors, such as age, history of myocardial infarction and National Institute of Health stroke scale (NIHSS) [20,21]. One study [21] found the history of myocardial infarction and NIHSS had a higher OR (2.26 and 1.18) for 90-day mortality, and the NLR had a weaker predictive ability with OR of 1.08.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [18,33] reported some independent predictors for mortality, such as age, NIHSS and the volume of infarct. With multivariate regression analysis, Maestrini [20] and Brooks [21] adjusted the outcomes with onset-to-treatment, gender, atrial fibrillation, systolic BP, recanalization, application of tissue plasminogen activator (tPA), and they found that NLR was independently associated with 90-day mortality. The study [19] that used univariate regression analysis also suggested that NLR at admission is a prognostic biomarker in acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Как в экс-периментальных моделях, так и у человека ин-сульт сопровождается быстрым (в течение часов) возрастанием числа лейкоцитов в перифериче-ской крови и усилением экспрессии генов про-воспалительных медиаторов, что свидетельствует о развитии системной воспалительной реакции в ответ на ишемическое поражение мозга [32,86]. Системное воспаление проявляется значимым увеличением соотношения нейтрофилов и лим-фоцитов [136], величина которого является про-гностическим маркером 60-и 90-суточной ле-тальности при ишемическом инсульте [12,120].…”
Section: системные проявления иммунного ответа на острую ишемиюunclassified